Eurasian Tree Sparrows, Risk for H5N1 Virus Spread and Human Contamination through Buddhist Ritual: An Experimental Approach - Gutiérrez, Ramona Alikiiteaga (Public Library of Science, 2011)
BACKGROUND: The Highly Pathogenic Avian Influenza H5N1 virus has dramatically spread throughout Southeast Asia since its first detection in 1997. Merit Release Birds, such as the Eurasian Tree Sparrow, are believed to increase one's positive karma when kissed and released during Buddhist rituals. Since these birds are often in close contact with both poultry and humans, we investigated their potential role in the spread of H5N1 virus. METHODOLOGY/PRINCIPAL FINDINGS: Seven series of experiments were conducted in order to investigate the possible interactions between inoculated and exposed birds, including sparrow/sparrow, sparrow/chicken, duck/sparrow. Daily and post-mortem samples collected were tested for H5N1 virus by real-time RT-PCR and egg inoculation. When directly inoculated, Eurasian Tree Sparrows were highly susceptible to the H5N1 virus, with a fatality rate approaching 100% within 5 days post-inoculation. Although transmission of fatal infection between sparrows did not occur, seroconversion of the exposed birds was observed. Up to 100% chickens exposed to inoculated sparrows died of H5N1 infection, depending on the caging conditions of the birds, while a fatality rate of 50% was observed on sparrows exposed to infected ducks. Large quantities of H5N1 virus were detected in the sparrows, particularly in their feathers, from which infectious particles were recovered. CONCLUSIONS/SIGNIFICANCE: Our study indicates that under experimental conditions, Eurasian Tree Sparrows are susceptible to H5N1 infection, either by direct inoculation or by contact with infected poultry. Their ability to transmit H5N1 infection to other birds is also demonstrated, suggesting that the sparrows may play a role in the dissemination of the virus. Finally, the presence of significant quantities of H5N1 virus on sparrows' feathers, including infectious particles, would suggest that Merit Release Birds represent a risk for human contamination in countries where avian influenza virus is circulating and where this religious ritual is practiced.